2005
DOI: 10.1002/ejoc.200400716
|View full text |Cite
|
Sign up to set email alerts
|

Steric Effects in Enantioselective Allylic Alkylation Catalysed by Cationic(η3‐Allyl)palladium Complexes Bearing Chiral Pyridine‐Aziridine Ligands

Abstract: Enantiopure N,N′‐bidentate ligands (N,N′)*, containing substituted aziridine and aza‐aromatic rings, were prepared from imines derived from (S)‐valinol or (R)‐phenylglycinol and heteroaromatic aldehydes (2‐pyridine‐, 6‐benzyl‐2‐pyridine‐, 2‐ and 8‐quinolinecarbaldehyde) by the addition of iPrMgCl and subsequent cyclisation of the 1,2‐amino alcohol moiety to aziridine. Crystalline [(N,N′)*(η3‐allyl)Pd][SbF6] complexes were prepared from these ligands and used as catalysts in the alkylation of sodium dimethyl ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…Chloro-diphenylphosphine was distilled under vacuum. Acid 2, 9c 1,3-diphenylprop-2-en-1-yl acetate (13a), 47 ethyl (1,3-diphenylprop-2-en-1-yl) carbonate (13b), 48 and di-m-chlorido-bis(Z 3 -1,3-diphenylallyl)dipalladium(II) (15) 49 were prepared following the literature procedures. Other chemicals and solvents used in workup and in crystallisations were used as received (Fluka and Aldrich).…”
Section: Experimental Materials and Methodsmentioning
confidence: 99%
“…Chloro-diphenylphosphine was distilled under vacuum. Acid 2, 9c 1,3-diphenylprop-2-en-1-yl acetate (13a), 47 ethyl (1,3-diphenylprop-2-en-1-yl) carbonate (13b), 48 and di-m-chlorido-bis(Z 3 -1,3-diphenylallyl)dipalladium(II) (15) 49 were prepared following the literature procedures. Other chemicals and solvents used in workup and in crystallisations were used as received (Fluka and Aldrich).…”
Section: Experimental Materials and Methodsmentioning
confidence: 99%
“…A similar inversion of enantioselectivity with a longer bridge was reported for pyridine-aziridine ligands. 29 It was found that modification on the 6-position of the pyridine ring caused reversal of the stereoselectivity for the allylic alkylation, similar to an increase in the chelate size. Ligand 34 catalyzed the reaction to afford the major product as the (R)-enantiomer.…”
Section: Catalytic Results For Palladium-catalyzed Allylic Alkylationmentioning
confidence: 97%
“…A similar inversion of enantioselectivity with a C6-pyridine substituent was reported for pyridine-aziridine ligands. 29 Changing the electronic properties of the substituents on the 4-position of the pyridine ring has no significant effect on the stereoselectivity of the reaction. Instead, the electronic properties of the substituents on this position only affected the reactivity of these ligands.…”
Section: Catalytic Results For Palladium-catalyzed Allylic Alkylationmentioning
confidence: 99%
See 1 more Smart Citation
“…At this point we assessed the possibility of using β‐amino alcohol 7 for the construction of new optically active, pyrrole‐containing molecules, such as aziridines by intramolecular cyclization and secondary amines through oxidative cleavage of the chiral auxiliary (Scheme ). For the first goal we followed the same protocol previously applied for the synthesis of analogous 1‐(2‐pyridyl)alkylaziridines 18b,18c. As a matter of fact, pyrrole–aziridines 9a , b , f were successfully obtained in high yields by treatment of β‐hydroxyamines 7a , b , f with triphenylphosphane and diethylazodicarboxylate (DEAD) in THF at room temperature.…”
Section: Resultsmentioning
confidence: 99%